Evaluation of the application efficiency of multicomponent ceramics as protective shielding and thermal barrier materials - Kozlovskiy, A.L.; Borgekov, D.B.; Tleulessova, I.K.; Zhumazhanova, A.T.; Moldabayeva, G.Zh.; Burkhanov, B.Zh.; Khametova, A.A. (Karagandy University of the name of academician E.A. Buketov, 2025)
The paper presents the comparative analysis results of the shielding characteristics of multicomponent ceramics obtained by mixing TeO2, CeO2, WO3, ZnO, Bi2O3 and ZrO2 oxides in various molar ratios, enabling acquisition of ceramics with a variable phase composition. According to the results of X-ray phase analysis, the addition of ZrO2 to the composition of composite ceramics leads to the formation of a monoclinic substitution phase ZrCeO2. The contribution growth of the latter results in strength properties growth due to a change in the concentration of interphase boundaries in the composition of ceramics. During the tests conducted for resistance to thermal effects capable of leading to destabilization of the crystalline structure, it was established that an increase in the contribution of ZrO2 in the composition of ceramics leads to an increase in resistance to thermally induced softening processes, and an increase in the stress resistance of ceramics during tests for thermal shock effects. During determination of the shielding characteristics of the studied ceramics, it was found that the formation of a stabilizing ZrCeO2 phase in the composition of multicomponent ceramics leads to an elevation in the shielding efficiency, as well as the stability of the preservation of shielding characteristics as a result of long-term thermal effects and thermal shock tests. Moreover, the greatest increase in the efficiency of the measured parameters is observed in the case of assessment of thermal insulation characteristics. The increase in the latter is more than 2.5 times compared to non-stabilized ceramics, which do not contain inclusions in the form of the ZrCeO2 phase.
Keywords: composite multicomponent ceramics; shielding materials; thermal shock exposure; stabilization; doping